2013
DOI: 10.1299/jtst.8.337
|View full text |Cite
|
Sign up to set email alerts
|

Entransy, Entransy Dissipation and Entransy Loss for Analyses of Heat Transfer and Heat-Work Conversion Processes

Abstract: Entransy is a parameter proposed in recent years to describe the potential of heat in an object. Its balance equation was established based on the energy equation of heat transfer, which contains entransy, entransy flow, entransy dissipation and entransy production due to heat source. It has been proved that the total entransy must be reduced whenever there is heat transfer in an isolated system, leading to entransy dissipation. Entransy dissipation and entransy-based thermal resistance can be used to optimize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(9 citation statements)
references
References 56 publications
(145 reference statements)
0
9
0
Order By: Relevance
“…Similarly, electrical potential energy stored in a capacitor is QV/2, and thermal potential energy stored in a system is UT/2. Thus, entransy (G) is defined as the half of the product of internal energy (U) and temperature (T) and expressed as [17][18][19][20][21][22][23][24][25][26][27];…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, electrical potential energy stored in a capacitor is QV/2, and thermal potential energy stored in a system is UT/2. Thus, entransy (G) is defined as the half of the product of internal energy (U) and temperature (T) and expressed as [17][18][19][20][21][22][23][24][25][26][27];…”
Section: Methodsmentioning
confidence: 99%
“…Exergy analyses at different conditions have been performed on heat exchangers and power plants by Geete et al and Ibrahim et al, and after analyses they found minimum exergy destruction is good for better outputs from thermal systems [12][13][14][15][16]. Chen et al, Feng et al, Guo et al and other researchers have worked on entransy concepts for heat exchanging devices, and they applied entransy dissipation, entransy dissipation-based thermal resistance and entransy dissipation number on thermodynamic systems for comparative performance analyses and concluded that these parameters should be minimum [17][18][19][20][21][22][23][24][25][26][27][28]. In this research work, rates of entropy generation, exergy destruction, entransy dissipation, entransy dissipationbased thermal resistance, entransy dissipation numbers, effectiveness and entropy generation numbers have been calculated at different operating conditions to get better conditions at which performance of counter flow doublepipe heat exchanger will be the best.…”
Section: Introductionmentioning
confidence: 99%
“…From the viewpoint of entransy, the entransy loss can be defined as the difference between the entransy flows into and out of the system, and it is the entransy consumed in the heat-work conversion [9,12,[22][23][24][25]. Therefore, we have…”
Section: Entransy Variation Associated With Work In Heat-work Conversionmentioning
confidence: 99%
“…In the analyses of thermodynamic cycles, Cheng and Liang [22] proposed the concept of entransy loss, which is the entransy consumed during the thermodynamic processes. Under some conditions, it was found that larger entransy loss leads to larger output power for the discussed systems [9,12,[22][23][24][25][26]. In heat pump systems, it was found that the system entransy does not decrease but increase, so the concept of entransy increase was proposed [26].…”
Section: Introductionmentioning
confidence: 99%
“…The EGR was taken as the optimization objective in the constructal design of the disc-shaped SGR [37]. The optimizations of transfer processes based on entransy theory have provided various useful guidelines for the designs of the transfer systems [15,20,22,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60]. Consider these situations, the ''disc-point'' model of the SGR with heat conduction and gas diffuser in Ref.…”
Section: Introductionmentioning
confidence: 99%